Poor Executive Functions among Children with Moderate-into-Severe Asthma: Evidence from WCST Performance - Taha, Haitham (Frontiers in Psychology, 2017)
Executive functions measures of 27 asthmatic children, with general learning difficulties, were tested by using the Wisconsin card sorting test (WCST), and were compared to the performances of 30 non-asthmatic children with general learning difficulties. The results revealed that the asthmatic group has poor performance through all the WCST psychometric parameters and especially the perseverative errors one. The results were discussed in light of the postulation that poor executive functions could be associated with the learning difficulties of asthmatic children. Neurophysiological framework has been suggested to explain the etiology of poor executive functions among children with moderate into severe asthma.